Revolusi Manajemen Pendidikan Berbasis Hadis dalam Menjawab Tantangan Disrupsi Teknologi dan Etika - Mirhabun Nadir; Ma’shum Thoyib; Desi Irianti; Achmad Khotib (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to examine how hadith-based education management at MAN Prafi is able to respond to the challenges of technological disruption and ethical crises in the digital era. The study uses a qualitative approach with a case study type. This study was conducted at MAN Prafi, Manokwari, West Papua Province, Indonesia. Data collection techniques include in-depth interviews, participant observation, documentation, and audio analysis. Data were analyzed using the Miles and Huberman interactive model consisting of data reduction, data presentation, and conclusion drawing. Data validity checks were carried out through triangulation of sources, methods, and observers. The results of the study conducted at MAN Prafi, Manokwari, West Papua Province, Indonesia show that the integration of hadith values ​​such as amanah, syura, and sidq has become the basis for managerial policies in schools. Religious teachers play a central role as agents of change in the process of value transformation and the formation of an ethical culture. In addition, adaptive strategies based on religious-humanistic have proven to be able to align the use of technology with Islamic moral values. This study contributes to the development of an Islamic education management model that is responsive to changes in the times while being based on solid religious values.